Pemberdayaan Umkm Gorden Sebagai Strategi Pengentasan Kemiskinan Berbasis Potensi Lokal Di Desa Deliksumber Gresik - Joko Arianto; Sri Roekminiati; Ika Devy Pramudiana; Sapto Pramono (Journal of Innovative and Creativity, 2025)
The empowerment of Micro, Small, and Medium Enterprises (MSMEs) producing curtains in Deliksumber Village is a strategic initiative successfully harnessing local potential to alleviate poverty. This program emphasizes not only economic enhancement but also the utilization of existing social and institutional capital within the community. Traditions of mutual cooperation and social solidarity serve as the main driving forces behind collaboration in production, marketing, and enterprise management. By forming MSME groups that support each other, community members share knowledge on sewing techniques, basic financial management, and digital marketing, thereby improving product quality and expanding market reach. Product innovations such as the use of local fabrics, customization according to orders, and collaborations with interior designers create added value, strengthen cultural identity, and enhance product competitiveness in the market. The success of this program is also supported by physical assets such as household-owned sewing machines, along with government support that provides training facilities and institutional facilitation. The strategic location of the village, situated near busy centers, further facilitates distribution and marketing, broadening markets and increasing community income. This program not only improves well-being through supplemental income but also fosters independence among women and the community at large. The transformation of sewing skills from passive to professional expertise demonstrates the effectiveness of an asset-based and socio-economic innovative approach. This success proves that community-utilized potential and assets, when integrated holistically, can offer sustainable solutions in poverty eradication. Moreover, the program’s achievement highlights the importance of synergy among community groups, local government, and entrepreneurs in creating a conducive ecosystem for MSME development based on local potential. This research indicates that the MSME curtain empowerment in Deliksumber is not just a success model of community-based economic development but also an innovative strategy to preserve cultural heritage through product innovation aligned with local cultural potential. This comprehensive multi-stakeholder approach is expected to serve as a reference for developing similar empowerment programs in other regions with comparable potentials.